2000
DOI: 10.1002/1096-9101(2001)28:1<67::aid-lsm1018>3.0.co;2-e
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic characterisation of carotid atherosclerotic plaque by laser induced fluorescence

Abstract: The accuracy for discrimination of the heterogeneous composition of the atherosclerotic plaque is still limited, due to superposition of the fluorescence emission of various plaque components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…The laser-induced fluorescence (LIF) spectroscopy is an optical method that assesses the interaction between light at a given wavelength and tissue (15,16), allowing tissue characterization based on fluorescence (17). Fluorescence has been applied in medicine as a diagnostic method for tumours, at several sites, premalignant lesions of the digestive tract, carotid atherosclerosis plaques and among other lesions (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…The laser-induced fluorescence (LIF) spectroscopy is an optical method that assesses the interaction between light at a given wavelength and tissue (15,16), allowing tissue characterization based on fluorescence (17). Fluorescence has been applied in medicine as a diagnostic method for tumours, at several sites, premalignant lesions of the digestive tract, carotid atherosclerosis plaques and among other lesions (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%
“…Different spectroscopic techniques, including fluorescence spectroscopy, Raman techniques, and near-infrared ͑NIR͒ spectroscopy, have been used to characterize normal tissues and plaques in human artery samples. Fluorescence spectroscopy has been used to study normal and atherosclerotic tissues based on endogenous or exogenous tissue chromophores, [14][15][16][17][18][19][20][21][22][23][24][25][26][27] successfully classifying normal and plaque artery tissues in vitro. In a more recent study, Marcu et al demonstrated a catheter-based timeresolved fluorescence spectroscopic technique for in-vivo dif-ferentiating and demarking macrophage content versus collagen content in a rabbit atherosclerotic model.…”
Section: Introductionmentioning
confidence: 99%
“…Significant interplay between absorption and scattering severely attenuates the fluorescence spectra, particularly in the presence of hemoglobin, making discrimination of plaque through blood a very difficult task. 40 A combined approach using fluorescence and diffuse reflectance spectroscopy has been proposed. 41 This approach may allow for the unambiguous interpretation of endogenous tissue fluorophores.…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%
“…A main limitation of fluorescence is the fact that tissue chromophores possess broad and overlapping absorption spectra. Significant interplay between absorption and scattering severely attenuates the fluorescence spectra, particularly in the presence of hemoglobin, making discrimination of plaque through blood a very difficult task 40 . A combined approach using fluorescence and diffuse reflectance spectroscopy has been proposed 41 .…”
Section: Fluorescence Spectroscopymentioning
confidence: 99%